MY SAY: Reconstructing the Silk Road - Razak, Dzulkifli Abd (2011)

(untitled)
Since time immemorial, Asia has been standing at a global crossroads, if we take the Silk Road as an example. Originating in Central Asia, the almost 7,000km route ran through major trade hubs to Europe and Africa. It extended from the city of Xi'an (formerly Chang'an, the capital of ancient China) in the northwest Shaanxi province to Europe via South and Central Asia. While the Silk Road generally referred to a land route, it also included the seas that were crossed for the exchange of materials, information and knowledge.